Evaluasi Kebijakan Keaksaraan Usaha Mandiri (KUM) di Kabupaten Pemalang Tahun 2011 - Syamy Anggoro Kasih (Journal of Politic and Government Studies, 2013)
Abstract :The study is about evaluation of Independent Business Literacy Policy (Keaksaraan Usaha Mandiri) conducted by Government of Pemalang Regency that began in 2011. The background of Policy is illiteracy issues unresolved until today when the literacy program has been implemented since the Dutch colonial era. The Policy Evaluation was conducted is done by three aspects, namely achievement of policy objectives, researching of the policy outcomes, and sustainability of the Policy. The purpose of the policy is to increase participation of citizens KUM learning program for literacy, therefore it can enhance empowerment and independence, and also maintain and preserve the ability of literacy. The results showes that the policy has been able to achieve the target set by the government and also it has impact in economic, sustainable of literacy and skill as well as cooking and make a stuff and benefit the residents learned after the program has been running. For sustainability of the policy, government, communities and the providers wants to continue the policy and also no capital to start a business.Keywords: evaluation of policies, literacy, independence and empowerment efforts.